PENINGKATAN SIFAT FISIKOMEKANIK FILM ALGINAT UNTUK TUJUAN SALUT ENTERIK MELALUI PEMBENTUKAN NANOKOMPOSIT - Gusti Ngurah Jemmy Anton Pra, I
Clay-containing polymeric nanocomposites (CPNC) is a polymer matrix added with nanoclay filler that was generally intended for coating. The aim of this incorporation was to improve the mechanical properties and also water vapor and gas permeability. Sodium alginate is a natural polymer that can dissolve in alkaline condition and swells in acid solution. It can be so used as a polymer for enteric coating. However, a film of pristine sodium alginate has a low mechanical properties. Sodium bentonite is one of natural clay and contains about 80% montmorillonite. The purpose of this research was to improve the mechanical properties of sodium alginate through incorporation with nanoclay sodium bentonite. The experiment was began by choosing the proper of swelling clay method (stirrer, ultraturax and sonication) at concentration of 5%. The swelled clay was than added in various concentrations of 0, 2, 3, 4 and 5% into solution of sodium alginate 1%. These mixtures were than formed a film by film casting method. The characteristic of films were evaluated by using the XRD, SEM, water vapor permeability and also the mechanical properties (tear resistance, tensile strength, percent elongation and modulus of elasticity). Nanocomposite solution was then applied to core tablet with active substance sodium diclofenac. The release of active substance from tablet were tested using USP Apparatus 3 (reciprocating cylinder). The clay swelled by stirrer, ultraturax and sonication produced the viscosity of 1263,33±5,77; 1740,00±0,00 and 2883,33±5,77 cPs respectively. The identification of nanocomposite films by XRD and SEM showed that the nanoclay experienced the exfoliation. Coefficient of water vapor permeability from each formula were 3,37±0,05; 2,23±0,12; 2,21±0,14; 2,12±0,00; dan 1,86±0,03 x10 3 g h -1 cm -1 mmHg -1 respectively. While the mechanical properties showed that the tear resistance of each formula were 6,86±0,00; 16,01±1,13; 16,99±2,47; 18,62±1,70 and 23,52±1,70 N respectively. Tensile strength were 17,15±0.00; 40,02±2,83; 42,47±6,17; 46,55±4,24 and 58,80±4,24 MPa respectively. Percent elongation were 18,97±0,69; 4,97±0.00; 6,11±0,62; 5,64±0,28 and 5,30±0,29. Mean while the modulus of elasticity for each formula were 90,48±2,90; 805,70±56,96; 694,12±58,03; 824,68±64,58, and 1108.70±20.32 MPa. Nanocomposite containing of 5% nanoclay gave tensile strength and modulus of elasticity which was higher than the other formula and it has a lower of water vapor permeability. This result could be suitable for enteric coating material. Based on the enteric coating tablet evaluation, this mixture can produced a smooth tablet without film defect and enabled to release the active substance in intestinal fluid more than 80% (Q+5%) for 45 minutes. In conclusion, nanocomposite at concentration 5% could be suitable as a coating material for tablet enteric coating. K